PERTUMBUHAN EKONOMI DAN DAMPAKNYA PADA LINGKUNGAN: STUDI KASUS PENGELOLAAN SAMPAH DI PROVINSI JAWA BARAT - Ramdani, Sandi Asep (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2024)
Inclusive and sustainable economic development has always been the main development goal of every region. Based on this, this research tries to analyze the effect of economic growth on environmental degradation by focusing on the amount of waste generation at the West Java Province during the 2013-2022 period. The research was carried out using quantitative methods using secondary data and data analysis using panel data regression with the Fixed Effect Model. Based on the results of the analysis, it showed that there is no evidence of the existence of the EKC curve in research on waste generation in West Java, GRDP per Capita has a positive but not significant effect on waste generation, while GDP per Capita squared has a negative and significant effect on waste generation. Apart from that, education level has a negative but not significant effect, the Gini ratio has a positive but not significant effect, while population density and number of industries have a negative and significant effect. Based on these findings, policies can be recommended in the form of support for the leading waste management sector in West Java, provision of waste management facilities in densely populated areas, and waste management education for the community.